Intervention of Bacterial Leaf Streak of Wheat Through Neem Mediated Copper and Zinc Hybrid Nanoparticles - Manzoor, Aleena; Ahmad, Hadeed; Aslam, Maryam; Atif, Muhammad (Journal of Agriculture and Biology, 2025)
Bacterial leaf streak (BLS), caused by Xanthomonas translucens pv. undulosa, is a significant disease affecting wheat crops, leading to considerable yield loss globally. In response to this, green-synthesized nanoparticles offer a promising alternative to traditional chemical treatments, providing both disease management and environmental sustainability. The study evaluated the effectiveness of green-synthesized nanoparticles, including Copper (Cu), Zinc (Zn), and their combination (Cu+Zn), in controlling bacterial leaf streak (BLS) in wheat. A greenhouse trial was conducted using a Completely Randomized Design (CRD) with three replicates for each treatment and nanoparticle concentration (0.25%, 0.50%, and 0.75%). The findings revealed that Cu+Zn nanoparticles achieved the highest reduction in disease incidence (20.5%), followed by Zn nanoparticles (25.6%) and Cu nanoparticles (28.7%) compared to the untreated control. Similarly, a field experiment designed as a Randomized Complete Block Design (RCBD) with three replicates per treatment supported these results. Cu+Zn nanoparticles reduced disease incidence to 23.8%, while Zn nanoparticles and Cu nanoparticles showed reductions of 27.9% and 31.2%, respectively. These findings highlight the potential of neem-mediated copper-zinc hybrid nanoparticles as an effective and environmentally friendly approach for managing bacterial leaf streak in wheat, offering a promising alternative to chemical pesticides.
Keywords: Copper (Cu), Zinc (Zn), and their combination (Cu+Zn)